William Morris' Position between Art and Politics. - Zinkiewicz, Grzegorz (Cambridge Scholars Publishing, 2016)
This volume re-evaluates the position of William Morris regarding contemporary perspectives on his artistic and political endeavours. Special emphasis is placed on the concepts and territories that lie in-between, both literally and metaphorically. This "in-between-ess" is the most remarkable quality of Morris, and secures him a unique position among his contemporaries, as well as inspiring new generations of scholars. Paradoxically, however, this aspect also contributes to a certain marginalization of Morris in studies devoted to "Eminent Victorians". Instead of speaking of ruptures, gaps or.